Polar Bear Distribution and Habitat Association Reflect Long-term Changes in Fall Sea Ice Conditions in the Alaskan Beaufort Sea - Gleason, Jeffrey S.; Rode, Karyn D. (ARCTIC, 2009)
The polar bear (Ursus maritimus) is considered an indicator species of ecosystem health because of its longevity, life-history requirements, reliance on sea ice (i.e., sea ice obligate), and position in the Arctic food web. Polar bear distribution and habitat association should both be reliable signals for environmental perturbation, as the bears respond behaviorally to changes in sea ice extent, the timing and duration of ice formation, and ablation. Polar bears and sea ice conditions were monitored as part of the annual fall bowhead whale (Balaena mysticetus) aerial survey in the Alaskan Beaufort Sea between 1979 and 2005. Habitats associated with polar bear sightings changed during the study, with fewer bears associated with ice (irrespective of ice type and percent) and more bears associated with land and open water. Large-scale differences were documented for both ice type and percent ice cover, particularly in September. In general, the pattern in September (and to a lesser extent in October) included a reduction in old ice and a concomitant increase in open water. In addition, there was an eastward and landward shift in polar bear sightings. From 1979 to 1987, polar bears were observed primarily on ice along the shelf break near Barrow, whereas from 1997 to 2005, polar bears were observed on barrier islands or along the mainland coast near Kaktovik. The changes in polar bear distribution and habitat association appear to reflect a behavioral response by polar bears to changes in ice (type and percent cover) and in the timing of ice formation and ablation. L’ours polaire (Ursus maritimus) est considéré comme une espèce indicatrice de la santé de l’écosystème en raison de sa longévité, des besoins de son cycle biologique, de sa dépendance de la glace de mer (c’est-à-dire la glace de mer obligatoire) et de la position qu’il occupe dans le réseau alimentaire de l’Arctique. La répartition de l’ours polaire et son association à un habitat devraient tous deux constituer des signaux fiables en matière de ...